Preliminary investigation of the practicality of an industrial training for engineering technology program – industries view - Jalani, Jamaludin; Mashori, Sumaiya; Norjali, Rasida; Sadun, Amirul Syafiq (Asian Research Publishing Network (ARPN)., 2016)
One of the important aspects of Engineering Technology (ET) program is the students must be able to apply a significant hands-on job throughout the program. Apart from laboratory work carried out at the university, the industrial training components can also contribute a significant practical work to enhance the skills of the students. In this study, the difference between ET and Engineering program is distinguished by proposing longer periods of industrial training in ET program. However, the effectiveness of longer periods of training must be investigated in order to find out whether this framework has to be retained for future training. For this, the university has structured the industrial training by imposing the students to undergo two (2) months training during the third (3rd) semester of year two (2), another two (2) months during the third (3rd) semester of year three (3) and finally, six (6) months during the last semester of fourth (4th) year (i.e. final semester). An interview has been conducted with two industrial panels to find out the effectiveness of the proposed training. A few suggestions and ideas given by both panels were considered for the development for industrial training syllabus in ET program.